Pengambilan Keputusan dalam Pelaksanaan Rujukan Puskesmas sebagai Fasilitas Kesehatan Tingkat Pertama (Decision Making in the Refferal Implementation at Public Health Center as First Level Health Facility) - Estik Ikka Indah Purwati; Nuryadi Nuryadi; Yennike Tri Herawati (Pustaka Kesehatan, 2017)
Public health center is a first level of health facility which collaboration with health care and social security agency must be organize a comprehensive health care. Based on P-Care application at 30 public health centers in district jember obtained 1 public health center which has not the disease refferal rate data as (100%), 12 public health center as (5%), 10 public health center as (5-10%) and 7 public health center over (10%). Based on these data can been conclusion that the disease refferal data which can be handled is still high and the refferal implementaion which is not appropiate at public health center in district jember. The purpose of this study was to identified decision making process in public health center refferal implementation which were not appropriate as first level of health facility.These study was a descriptive. This study was held at 29 public health centers in district Jember on February-March 2016. Sample of these study was 29 health centers. Result showed that of 29 public health center (100%) identified having problem of the refferal which were not appropriate. All public health center in district jember make data collection. All public health center make alternative solution development. All public health center make problem solving evaluation. All public health center make the best alternative election. Alternative preferred by public health center as the best alternative was education and motivation. Keywords: Decision Making, Refferal